THE ROLE OF N-TERMINAL PRO-C-TYPE NATRIURETIC PEPTIDE AS A DIAGNOSTIC BIOMARKER OF PULMONARY HYPERTENSION IN COPD PATIENTS - V. V. Gaynitdinova; L. A. Sharafutdunova; S. N. Avdeev (Евразийский Кардиологический Журнал)
Objective. Available data on the diagnostic value of determination of the concentration N-terminal pro-C-type natriuretic peptide (Nt-proCNP) to predict pulmonary hypertension (PH) in patients with COPD are few. Aim. To determine the concentration of NT-proCNP in COPD patients and evaluate its diagnostic value for the prediction of PH in COPD. Methods. The study involved 47 patients with COPD (GOLD II-IV, age 59,49±0,63 years, disease duration 13,7±0,63 years, smoking history 23,09±0,93 packs/years). NT-proCNP concentration in serum was assessed by ELISA technique (test Biomedica Medizinprodukte GmbH & Co KG, Austria). The pulmonary artery systolic pressure (SPAP) was analyzed by using a color-Doppler technique. Results. Concentrations of NT-proCNP were significantly higher in COPD patients with PH (SPAP 40-55 mmHg, n=16) or severe PH (SPAP ≥55 mmHg, n=10) than in patients without PH (SPAP < 40 mmHg, n=21): 4.14±0.51 pg/ml, 5.26±0.21 pg/ml and 1.42±0.03 pg/ml (p